مفهوم الإصلاح في الإسلام :‏ ‏عمر بن عبد العزيز نموذجا /‏ - رواس، غازي بن سعيد البحر
This study analyzes the concept of reform in Islam (Mafhum al-Islah fi al-Islam) taking as an example the period of the Caliph'Umar Ibn 'Abdul 'Aziz. The study examines the concept of reform in four different fields related to religious reform (al-Islah al-Dini), social reform (al-Islah al-Ijtima'i), political reform (al-Islah al-Siyasi), and economic reform (al-Islah al-IqtiÎsadi) in order to reach into general definition of reform in Islam. The study analyzes the reform in these fields during the era of 'Umar Ibn 'Abdul 'Aziz. The method of data analysis relies on the historical analytical approach. The data for this research is derived from major sources of no-survey data, namely theoretical, historical, sociological and political studies published in books, articles, journals and newspapers that belong to various periods of time. Statistical data is utilized whenever necessary, but in the final analysis the thesis is primarily qualitative rather than quantitative. The results of the study indicate that the charisma and leadership qualities of 'Umar Ibn 'Abdul 'Aziz was a uniform consideration behind the reform achievement in all four fields of reform analyzed by the case studies. However, the upbringing of 'Umar Ibn 'Abdul 'Aziz and his gradual uprising from within the Umayyah family contributed tremendously to the success of his reform. Overall, the study found that internal reform, rather than revolutions and externally-imposed reforms, are bound to succeed and contribute to some degree of institutionalization of reform in Islamic countries.